PELAYANAN PENCATATAN PERNIKAHAN OLEH KUA DI KABUPATEN PEMALANG JAWA TENGAH The Marriage Registration Service Offered by Office of Religious Affairs in Pemalang Central Java - Marmiati Mawardi (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2017)
Marriage is sacred agreement between man and woman to build a family and to have descendants. Based on the law Number 1 1974 on marriage, a marriage for Muslim has to be registered at an office of religious affairs (KUA). This research aims to know the quality of services offered by KUA on marriage and to understand the consumers’ satisfaction on such service. This will look at the gap between of consumers’ needs. This study uses a quantitative approach and Likert scale in order to measure the consumers’ satisfaction index on marriage service. Data were collected by spreading questioners to the selected respondents which are people using such service in Pemalang district. Findings of this study show that the consumers’ satisfaction index is 86.96; it means that the marriage service is categories as good. Four among five indicators depict that are very good, it means that the service given by KUA is very gratified. One indicator categorized as a good is tangible indicator. Although it is generally good, it still needs to be improved. Meanwhile, the gap between the consumers’ perceived and expected service tends to be in good score. This is due to the score of consumers expectation is more than the score of the real service gained by the consumers.